Analysis of Financial Feasibility of Kerupuk Kulit in Tambang Sub-District, Kampar Regency (Case Study of UD Kerupuk Kulit Jon Kenedi) - Novian; Yeni Kusumawaty; Elsa Azzahra (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2025)
This study aims to analyze the financial feasibility of the agroindustry of UD Kerupuk Kulit Jon Kenedi in Tambang District, Kampar Regency. The research uses a case study method with a quantitative approach. Data was obtained through interviews, observations, and documentation. The analysis was conducted using the Revenue Cost Ratio (R/C) and profitability ratios, which include Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Asset (ROA), and Return on Equity (ROE). The results of the study show that this business is feasible to run and develop. The R/C value > 1 indicates that the business is in an efficient condition, and the profitability ratio provides positive results every year, which reflects the business's ability to generate profits consistently. Nonetheless, this business still has weaknesses in terms of financial management and a lack of product innovation. Therefore, systematic financial recording and the development of managerial and marketing strategies are needed to increase the competitiveness and sustainability of the business in the future.